Feasibility and Safety of Clipless and Sutureless Laparoscopic Adrenalectomy: A 7-Year Single Center Experience - Simforoosh, Nasser; Shakiba, Behnam; Dadpour, Mehdi; Mortazavi, Seyyed Erfan; Hamedibazaz, Hamid Reza; Mahdavi, Mahdyar (Urology Journal, 2020)
Purpose: Laparoscopic adrenalectomy (LAD) is considered the gold standard surgical method for resecting adrenal tumors. To date, only few small studies have investigated the safety of clipless laparoscopic adrenalectomy in which the adrenal vessels were controlled by the LigaSure system or bipolar coagulation. The aim of the present study was to evaluate the safety and feasibility of sutureless and clipless laparoscopic adrenalectomy operations performed in our center. Materials and Methods: All patients with functional adrenal tumors, nonfunctional adrenal tumors larger than 5 cm and secondary adrenal metastases from the kidneys, lungs or breasts who had underwent an LAD procedure between 2012 to 2019 were included in our study. In all of the cases, complete coagulation of adrenal veins was achieved through bipolar cautery and no vascular staplers, clips or other energy sources were used for controlling the adrenal vessels whatsoever. Outcomes of interest included operation time, length of hospital stay, changes of serum hemoglobin level, and occurrence of major complications. Results: Of a total 251 patients, unilateral right and left-side adrenalectomy was performed in 168 and 67 cases, respectively, and 16 cases had underwent bilateral adrenal resection. The mean age (SD) of patients was 40.7 (13.6) years old at the time of operation and the mean size (SD) of the adrenal lesions was 5.2 (3.1) cm as measured by the greatest diameter. Histological examination showed that the most common pathology of the resected adrenal glands was pheochromocytoma (n=78). None of the laparoscopic operations required a conversion to open surgery. Also, major bleeding or other serious complications did not occur in any of the cases either intraoperatively or postoperatively. Conclusion: Clipless and sutureless laparoscopic adrenalectomy seems to be feasible and safe for removing adrenal tumors. Moreover, bipolar cautery is associated with an acceptable outcome for vessel closure.